PERAN SOSIAL PEREMPUAN DALAM ISLAM: KAJIAN HISTORIS-NORMATIF MASA NABI DAN KHULAFA’ RASYIDUN - Masruri, M. Hadi (EGALITA, 2012)
The debate on women’s social role in Islam is an endless issue. What hasbeen done by contemporary muslim thinkers to cover women issues is notenough to influence central feminism issue, gender equality and genderequity. It can be shown from the stereotype for women to limit women’ssocial role only in domestic area still exists. The stereotype on womenis based on the understanding religious doctrine which is inherited byprevious generation and it is considered to have historical root in Prophet’stradition and His followers. This writing tries to prove that   in the age ofthe Prophet and the age of khulafa ar Rasyidun can be the pilot project ofsocial role of women historically as well as normatively. At least, womenplayed significant role during that age in social, economics, and politics areas. All the facts of women’s role are included within Qur’an and hadith and they are also released in classical history of Islam such as Tarikh alThabariand Thabaqat Ibn Sa’ad.